(untitled) (Perner’s Contacts, 2015)
This paper deals with the issue of road safety and with factors affecting the road safety. The factors are divided into three groups: driver behaviour, construction and condition of the vehicle and condition of infrastructure. The paper also deals with the issue of alcohol that also has influence on the road safety.